Evaluación de medios de cultivo in vitro para especies forestales nativas en peligro de extinción en Ecuador - Campos, Jorge (2018)
Evaluation of in vitro culture media for native forest species in danger of extinction in Ecuador. The native species Myroxylon balsamum (balsam), Tabebuia crhysantha (guayacán) and Tabebuia billbergii (blackwood), are endemic forest species of the dry forest of the coast of Ecuador and Peru. The objectives of the research were: i) to develop a protocol for establishing, multiplying micropropagated plants in vitro conditions for the establishment of endangered native species in southern Manabi, and ii) defining the means of cultivation and disinfection protocols suitable for in vitro reproduction of threatened native species, using different concentrations of Povidyn®, NaClO + Tween + HgCl2 and exposure times for the establishment. According to the results in the in vitro establishment phase of explants of M. balsamum, T. crhysantha and T. billbergii, it was demonstrated that the application of Povidyn® for 20 minutes + 15% NaClO + 2 drops Tween for 5 minutes + 0.5% HgCl2 for 5 minutes, significantly reduces the contamination of the explants by microorganisms, reaching 90%, 87% and 88% respectively of live explants, free from contamination by fungi and bacteria at 30 days of evaluation. In the in vitro multiplication phase, the MS medium supplemented with 2 mg.l-1 BAP + 1 mg.l-1 ANA, allowed to generate 80%, 82% and 87 of healthy shoots in M. balsamum, T. crhysantha and T. billbergii respectively. The rooting of outbreaks of the three species in combined doses of BAP / AIB and BAP / ANA, had no effect. In vitro production of plant material selected from M. balsamum, T. crhysantha and T. billbergii, confirms the usefulness of micropropagation over the use of conventional techniques.